Teaching English Speaking Skills to Thai Students as a Foreign Language by Non-Thai Pre-Service Teachers: Strategies and Obstacles - Rani Meilani; Pirman Ginting; Yenni Hasnah (Universitas Muhammadiyah Enrekang, 2024)
The objective of this study is to investigate efficient methods for improving the English-speaking abilities of Thai students, implemented by non-Thai pre-service instructors. Additionally, this research attempts to identify and overcome any potential challenges that may develop throughout the teaching process. The study used a qualitative technique and descriptive case study design to examine data collected from in-depth interviews and questionnaires. The findings indicate that non-Thai pre-service teachers employ many successful ways to enhance the English-speaking abilities of Thai students. Nevertheless, obstacles like language and cultural barriers continue to be significant issues. This research also emphasizes the significance of hands-on experience in negotiating these challenges. However, there is a need for more improvement in institutional support in order to boost teacher effectiveness and improve student results. The study's implications are to facilitate cross-cultural education and enhance educational advancement in Thailand's linguistically varied setting.